Preoperative platelet aggregation predicts perioperative blood loss and rethoracotomy for bleeding in patients receiving dual antiplatelet treatment prior to coronary surgery - Plicner, Dariusz; Mazur, Piotr; Hymczak, Hubert; Stoliński, Jarosław; Litwinowicz, Radosław; Drwiła, Rafał; Undas, Anetta (Thrombosis research, 2015)
Patients scheduled for coronary artery bypass graft surgery (CABG) are commonly treated with clopidogrel. We sought to assess the relation between preoperative platelet aggregation and bleeds in CABG patients on clopidogrel. In a case-control study, we compared 52 consecutive patients undergoing isolated CABG on aspirin and clopidogrel 75mg/d versus 50 controls on aspirin monotherapy. Platelet aggregation induced by 10μmol/l adenosine di-phosphate (ADP) in platelet-rich plasma was measured in subjects on clopidogrel within 5days prior to surgery. ADP-induced aggregation of ≥50% was used to define subjects with satisfactory inhibition of platelet reactivity. In 29 patients with preoperative ADP-induced aggregation ≥50%, compared with 23 subjects with aggregation <50%, lower chest-tube drainage volumes (after 6h, p=0.002; and 12h, p=0.001) and fewer rethoracotomies were observed (p=0.03). The former group was characterized with lower transfusion rates of packed red blood cells (p=0.009), platelet concentrate (p=0.04) and fresh frozen plasma (p=0.001). Patients with ADP-induced aggregation ≥50% did not differ from untreated controls regarding the postoperative drainage, transfusions and rethoracotomy. The incidence of thromboembolic events and death during perioperative period were similar in all groups. Multivariate logistic regression identified ADP-induced aggregation <50% as the only independent predictor of rethoracotomy (OR=2.94 [1.12-7.75], p=0.029). Patients on aspirin and clopidogrel <5days before CABG who had preoperative ADP-induced platelet aggregation ≥50% have bleeding risk similar to those receiving aspirin monotherapy. Reduced platelet reactivity to ADP can predict postoperative bleeding in CABG patients on dual antiplatelet therapy. •We assessed how LTA predicts CABG–related bleeding on aspirin and clopidogrel•Patients undergoing CABG on DAPT were compared with those on aspirin monotherapy•LTA predicted bleeding in patients exposed to clopidogrel <5days before CABG•ADP-induced platelet aggregation <50% was associated with rethoracotomy•ADP-induced platelet aggregation ≥50% meant bleeding risk similar to aspirin monotherapy